The role of the educational supervisor in developing teachers’ functional performance at the post-basic education schools in Muscat governorate: teachers' perspectives = دور المشرف التربوي في تطوير الأداء الوظيفي للمعلمين في مدارس التعليم ما بعد الأساسي بمحافظة مسقط: دراسة من وجهة نظر المعلمين - Alhadidi, Ibrahim Ali Mubarak; Al-Hidabi, Dawood Abdulmalek Yahya (OCERINT International, 2020)
This quantitative study discusses the role of the educational supervisor in developing teachers’ performance at the in the post-primary education schools in Muscat Governorate, through revealing the supervisory practices of the educational supervisors, as well as detecting the differences in the study sample responses according to (gender and experience) variables. To achieve these objectives; the researcher used descriptive analytical method, and designed a questionnaire consisting of (30) paragraphs divided into five areas: (human relations, planning, training and professional growth, field monitoring, assessment and tests). The study population consists of (1440) teachers of post-primary schools in the Governorate of Muscat. The random sample consists of (341) male and female teachers. After the data descriptive analysis through the statistical processing of the SPSS program, the findings revealed that: the role of the educational supervisor in the development of the teachers’ performance in the area of (human relations) was big, while the supervisors’ practices in areas of (Planning, training and professional growth, field follow-up, evaluation and testing) were at medium levels according to the teachers’ point of view. There were statistically significant differences at the mean level (α ≥ 0.05) according to the gender variable in favor of the male teachers. There were no statistically significant differences for the experience variable. ******************************************************************************** هدفت هذه الدراسة الكمية إلى تشخيص دور المشرف التربوي في تطوير الأداء الوظيفي للمعلمين، في مدارس التعليم ما بعد الأساسي بمحافظة مسقط، وذلك من خلال الكشف عن الممارسات الإشرافية للمشرفين التربويين في المجالات المختلفة، وكذلك الكشف عن الفروقات في متوسطات استجابات أفراد عينة الدراسة، وفقًا لمتغيري الدراسة: (النوع، والخبرة). ولتحقيق أهداف الدراسة استخدم الباحث المنهج الوصفي التحليلي، وأعد استبانة تتكون من (30) فقرة موزعة على خمسة مجالات: (العلاقات الإنسانية، التخطيط، التدريب والنمو المهني، المتابعة الميدانية، التقويم والاختبارات). تكون مجتمع الدراسة من جميع المعلمين لمدارس التعليم ما بعد الأساسي في مدارس محافظة مسقط؛ الباغ عددهم (1440) معلم ومعلمة، لجمع البيانات تم أخذ عينة بالطريقة العشوائية المنتظمة تتكون من (341) معلم ومعلمة. بعد التحليل الوصفي في معالجة البيانات إحصائيا عن طريق برنامج (SPSS ) توصلت الدراسة إلى نتائج لعل من أهمها: كان دور المشرف التربوي في تطوير الأداء الوظيفي للمعلمين في مجال (العلاقات الإنسانية) بدرجة كبيرة، بينما كانت ممارسات المشرف التربوي في تطوير الأداء الوظيفي للمعلمين في المجالات (التخطيط، التدريب والنمو المهني، المتابعة الميدانية، التقويم والاختبارات) بدرجة متوسطة من وجهة نظر المعلمين. كما أظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية عند مستوى الدلالة ( 0.01 ≥ α ) وفقًا لآراء أفراد العينة تبعًا لمتغير (الجنس) لصالح المعلمين، وعدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة ( 0.05 ≥ α ) تبعًا لمتغير الخبرة حسب آراء عينة الدراسة.